CHROMagarTM Candida Plus: A novel chromogenic agar that permits the rapid identification of Candida auris. (11th June 2020) - Borman, Andrew M; Fraser, Mark; Johnson, Elizabeth M
Abstract: Candida auris is a serious nosocomial health risk, with widespread outbreaks in hospitals worldwide. Successful management of such outbreaks has depended upon intensive screening of patients to identify those that are colonized and the subsequent isolation or cohorting of affected patients to prevent onward transmission. Here we describe the evaluation of a novel chromogenic agar, CHROMagar TM Candida Plus, for the specific identification of Candida auris isolates from patient samples. Candida auris colonies on CHROMagar TM Candida Plus are pale cream with a distinctive blue halo that diffuses into the surrounding agar. Of over 50 different species of Candida and related genera that were cultured in parallel, only the vanishingly rare species Candida diddensiae gave a similar appearance. Moreover, both the rate of growth and number of colonies of C. auris recovered from swabs of pure and mixed Candida species were substantially increased on CHROMagar TM Candida Plus agar when compared with growth on the traditional mycological isolation medium, Sabouraud dextrose agar. Taken together, the present data suggest that CHROMagar TM Candida Plus agar is an excellent alternative to current conventional mycological media for the screening of patients who are potentially colonized/infected with Candida auris, can be reliably used to identify this emerging fungal pathogen, and should be tested in a clinical setting. Lay Abstract: Candida auris is a novel pathogenic yeast that has been associated with large hospital outbreaks across several continents. Affected patients become colonized, predominantly on the skin, with large quantities of C. auris which they then shed into the hospital environment. Identification of C. auris is challenging using routine laboratory methods, and time consuming when patients are colonized with a mixture of different Candida species. Here we demonstrate that a novel chromogenic agar, CHROMagar TM Candida Plus, permits the rapid differentiation of C. auris from a wide range of other yeast species and is potentially ideally suited to screening of patients that are suspected of being colonized or infected with this medically important yeast.